Pengaruh Jumlah Pelanggan Listrik, Daya Terpasang, dan Pemakaian Listrik Kelompok Bisnis terhadap Penerimaan Pajak Penerangan Jalan Kota Banjarbaru Tahun 2016-2020 - Kamil, Muhammad Ikhlasul; Saleh, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study was conducted to determine the influence of the number of electricity customers, installed power, and electricity usage from business groups on the receipt of street lighting tax in Banjarbaru City in 2016-2020. This study uses quantitative descriptive research with multiple linear regression analysis methods and time-series data from 2016 to 2020. The sampling technique in research used the saturated sample method. The results showed that the number of electricity customers, installed power, and electricity usage of business groups partially and simultaneously positively and significantly influenced the tax revenue of street lighting in Banjarbaru City.